Diseño de un sistema de implementación Bpms para la Planta Faenadora Proame en el cantón Salcedo - Timagsi Mendoza, Jessica Elizabeth (2022)
The present degree work consists of designing a system of Good Manufacturing Practices (GMP) in the company ̈PROAME ̈ located in the canton Salcedo province of Cotopaxi. For the realization of the research project, the Technical Regulation ARCSA- DE-067-2015-GGG was taken to the Technical Regulations ARCSA- DE-067-2015-GGG the same that is the Technical Standard that replaces the GMP for Processed Foods and the assurance of the quality and safety of the products. Initially, the ARCSA standard was revised through a current assessment of the company, to identify the slaughtering processes, since it allowed us to apply a check lis that includes two requirements required by current regulations in Ecuador through which the following aspects are identified: Facilities, equipment and utensils, hygienic manufacturing requirements, raw materials and inputs, production operations, packaging, labeling and packaging, storage, distribution, transport and quality assurance. As a result, 67,91% were obtained in compliance, 25,37% did not comply and 6,72% did not apply, finally these results were prepared a Manual of instructions (BPM) this plan is aimed at complying with the requirements of the regulations, for which the standardized operating procedures (SOP) and standardized operating procedures sanitation (SOPs) were elaborated, according to the needs found for compliance with the gradual plan, and so that the microenterprise can market safe products suitable for human consumption.